Genetic Counseling in Huntington's Disease: Potential New Challenges on Horizon? - Migliore, Simone; Jankovic, Joseph; Squitieri, Ferdinando (Frontiers in Neurology, 2019)
Huntington’s disease (HD) is a rare, hereditary, neurodegenerative and dominantly transmitted disorder affecting about 10 out of 100,000 people in Western Countries. The genetic cause is a CAG repeat expansion in the huntingtin gene (HTT), which is unstable and may further increase its length in subsequent generations, so called anticipation. Mutation repeat length coupled with other gene modifiers and environmental factors contribute to the age at onset in the offspring. Considering the unpredictability of age at onset and of clinical prognosis in HD, the accurate interpretation, a proper psychological support and a scientifically sound and compassionate communication of the genetic test result are crucial in the context of Good Clinical Practice and when considering further potential disease-modifying therapies. We discuss various genetic test scenarios that require a particularly careful attention in psychological and genetic counseling and expect that the counseling procedures will require a constant update.